Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1080/17482960802430781
|View full text |Cite
|
Sign up to set email alerts
|

Social economic costs and health-related quality of life in patients with amyotrophic lateral sclerosis in Spain

Abstract: Amyotrophic lateral sclerosis (ALS) is a process that leads to the functional disability of the individual in a relatively short period of time, with a very important limitation of autonomy and affecting the quality of life. We wished to determine the economic burden (direct and indirect costs), as well as health-related quality of life (HRQoL) in patients with ALS in Spain. A cross-sectional study was carried out on 63 patients with ALS during 2004. A retrospective assessment of the use of resources was obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 23 publications
4
49
2
1
Order By: Relevance
“…Fragmented disease knowledge means that care is not optimal, and there are significant differences in the infrastructure, expertise, diagnostic procedures, time to diagnosis, strategies and outcome. In analogy to other rare diseases it can be expected that this diversity has a negative impact on health outcome and on socio-economics (Brimley et al 2013;Linertov a et al 2012;López-Bastida et al 2008;López-Bastida et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Fragmented disease knowledge means that care is not optimal, and there are significant differences in the infrastructure, expertise, diagnostic procedures, time to diagnosis, strategies and outcome. In analogy to other rare diseases it can be expected that this diversity has a negative impact on health outcome and on socio-economics (Brimley et al 2013;Linertov a et al 2012;López-Bastida et al 2008;López-Bastida et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Although some countryspecific research on a limited set of rare diseases has been done on HRQOL and cost-of-illness [8][9][10][11][12], cross-national research on the socio-economic impact of rare diseases is still lacking in the EU.…”
mentioning
confidence: 99%
“…For example, in Denmark, Jennum et al (14) also found costs were highest in the index month, sharply rising during the months before diagnosis. Other ex-U.S. studies have found ALS costs increase with disease severity (4)(5)(6)(7)(8) and have connected rising costs to characteristics of disease progression such as wheelchairs and ventilators (4,5,8). However, the actual costs associated with ALS and when or how they are distributed across disease progression vary, indicating that the cost of ALS is multifactorial and likely to be dependent on country-specific healthcare policies.…”
Section: Discussionmentioning
confidence: 99%
“…No cure exists and the only drug shown to increase survival does so modestly (2). ALS management is primarily supportive (3), increasing with time and requiring greater assistance and intervention leading to escalating cost burden (4)(5)(6)(7)(8). Despite this burden, little has been published on costs associated with disease progression in patients with ALS (9).…”
Section: Introductionmentioning
confidence: 99%